Influence of green infrastructure objects for quality of surface runoff (on the example of green roofs in Kharkiv) - Maksymenko, Nadiya; Burchenko, Svitlana; Utkina, Kateryna; Buhakova, Marharyta (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Relevance. Modern urbanization processes in Kharkiv are accompanied by an increase in anthropogenic pressure on the natural component, compaction of buildings and reduction of green areas. The concept of green infrastructure is used in many countries around the world; it is the best way to reorganize urban space into modern cities. The purpose of the article is a determination of quality changes of water runoff after passing through of green roofs in Kharkiv, Ukraine. Material and methods. A green roof is the roof of a build, partially or completely covered with vegetation and soil layer. Green roofs are divided into “intensive” and “extensive” types. In the research was studied the frequency of use of green roofs in construction and landscaping on the example of Kharkiv, was conducted an inventory of green roofs in Kharkiv. As the number of green roofs in Kharkiv is rather small, is optimal to choice the particular test sites for research. For chemical analysis, were taken samples of snow, surface runoff from the flat, and sloping green roofs and roof without greening for the content of pollutants. Chemical analysis of the samples was performed by the Laboratory of Analytical Ecological Research of V.N. Karazin Kharkiv National University. The laboratory has the attestation and certificate of ISO 10012:2005 № 01-0155/2019. The study determined the following indicators: pH, nitrites, nitrates, transparency, smell, turbidity, chlorides, general rigidity, total alkalinity, ammonia, zinc, copper, manganese, cadmium, total iron, chromium. Two types often represent green roofs in Kharkiv: parking roofs and cellars. Points of samples are located at Shevchenkivsky and Kholodnohirsky districts. Results and discussion. Results of a study of snow and runoff sampling after a green roof and a roof without landscaping show that most water quality indicators improve after water passes through green areas. Thus, at points the pH, general rigidity, alkalinity, concentration of chlorides, chromium are decrease. The green roof of the first point (parking) also reduces the concentration of nitrites, ammonia, zinc and manganese. The concentration of iron also decreases in the second point. However, there is an increase in the concentration of heavy metals in the water due to their accumulation in the substrate of the green roof. The results of the study are can be used by the Post-Soviet countries, as previously the impact of surface runoff was considered only in terms of the flow of pollutants from storm sewers to water bodies. Conclusion. The results of the study indicate that green roofs contribute to the treatment of runoff, natural replenishment of surface water bodies and groundwater and reduce the load on municipal wastewater treatment plant.